The Formulation of Lotion Preparations of Betel Leaf Extract (Piper betle) - Ingenida Hadning; Putri Kurnyaningtyas; Muhammad Thesa Ghozali (Journal of Fundamental and Applied Pharmaceutical Science, 2020)
Betel leaf (Piper betle) contains an essential oil that has extreme antiseptic power (bactericidal and fungicidal). Betel leaf (Piper betle) can be used in the treatment of Tinea versicolor or known in the community as panu. However, its use in the form of leaves is considered impractical by the public and also difficult to obtain. This research formulated betel leaf (Piper betle) into lotion preparations, so its use in the community can be more practical. This study aims to determine the type and concentration of the suspending agent used to produce lotion preparations from betel leaf extract (Piper betle), which has optimal physical quality. This research was an experimental study. The distillation of betel leaf (Piper betle) was carried out to get essential oils. The essential oils of betel leaf (Piper betle), which was used as an active substance in formulations, was 5%. Suspending agents that were used in this study were Arabic gum with concentrations of 10%, 15%, 20%, and CMC Na, with concentrations of 0.25%, 0.5%, and 1%. The formulation of lotion preparations included organoleptic observation, pH test, homogeneity test, and adhesion test. Based on the physical quality test of the lotion preparations that had been conducted, it can be concluded that the lotion preparations of betel leaf extract with 20% concentration of Arabic Gum suspending agent had physical qualities in accordance with lotion dosage criteria.